Ryan Quinn and the lion's claw - McGee, Ron (McGee, Ron. Ryan Quinn, 2017)
Ryan Quinn and his best friend, Danny, stowaway on a plane to Africa in an attempt to save two revolutionary musicians whose identities have been compromised by a traitor within the Emergency Rescue Committee, while Ryan's parents, and ERC operatives, try to track the turncoat back in New York.